Successful Treatment of Ulcerative-Type Pyoderma Gangrenosum with a Combination Therapy of Oral Prednisolone, Vacuum-Assisted Closure, and Skin Grafting - Hiroyuki Goto; Yoshimoto Okada; Seimi Watanabe; Kanako Danno; Shinya Yamamoto; Ryohei Ishiura; Yuichi Nakayama; Kohei Mitsui; Ayaka Ueki; Yasuo Nakai; Mitsunaga Narushima; Keiichi Yamanaka (Karger Publishers, 2021)
Pyoderma gangrenosum (PG) is a relatively rare inflammatory skin disease that progressively causes necrotic ulceration mainly on the lower extremities and trunk. Systemic corticosteroid is considered a first-line treatment for PG as it facilitates wound healing; however, several cases where tumor necrosis factor-α inhibitors, adalimumab and infliximab, were administered showed good response. For intractable PG with a large ulcer or problematic epithelization, chemical or mechanical debridement of necrotic tissue in combination with skin grafting may be necessary to promote wound healing. Our report presents a case of intractable ulcerative PG requiring oral prednisolone and skin grafting. Although mechanical debridement was performed, granulation was poor; therefore, after the PG activity became quiescent, we utilized a vacuum-assisted closure (VAC) system to promote granulation and adaptation of the grafted skin. Although more cases are required for a definitive conclusion, the VAC system may be a choice for PG with large ulcers.